Post-traumatic elbow stiffness: Pathogenesis and current treatments. (February 2020) - Zhang, Dafang; Nazarian, Ara; Rodriguez, Edward K
Post-traumatic elbow stiffness is a major cause of functional impairment after elbow trauma. A stiff elbow limits patients' ability to position their hand in space for optimal use of their upper extremities, and as such, is a frequent indication for reoperation. This article reviews current concepts on the pathogenesis of post-traumatic elbow stiffness. Current nonoperative treatment options include therapy, bracing, and manipulation under anesthesia, while operative treatment options include arthroscopic and open arthrolysis. The pros and cons of various treatment options are discussed, with a focus on the evidence supporting their use, the expected functional gains, and associated complications. Future directions in post-traumatic elbow stiffness are highlighted.